2011
DOI: 10.1007/s11244-011-9708-8
|View full text |Cite
|
Sign up to set email alerts
|

Coke Formation on Pt–Sn/Al2O3 Catalyst in Propane Dehydrogenation: Coke Characterization and Kinetic Study

Abstract: The influences of gas compositions on the rates of coke formation over a Pt-Sn/Al 2 O 3 catalyst are studied. The coke formed on the catalyst is characterized by thermal gravimetric analysis, IR spectroscopy, Raman spectroscopy and elemental analysis. Two kinds of coke are identified from the TPO profiles and assigned to the coke on the metal and the coke on the support, respectively. The coke formed on the metal is softer (containing more hydrogen) than that formed on the support. The rate of coke formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(112 citation statements)
references
References 39 publications
8
104
0
Order By: Relevance
“…The spent (coked) catalysts had a peak at about 492°C in DTA spectrum and also there was a sharp slope in TG curve at the same temperature range that was the result of the coke oxidation [31]. Between 400 and 500°C, weight loss can be assigned to the removal of easily oxidizable carbonaceous species like amorphous carbon [32][33][34]. Furthermore, the comparison between DTA profiles of the fresh and coked catalysts indicated that the fresh catalyst did not contain any coke.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…The spent (coked) catalysts had a peak at about 492°C in DTA spectrum and also there was a sharp slope in TG curve at the same temperature range that was the result of the coke oxidation [31]. Between 400 and 500°C, weight loss can be assigned to the removal of easily oxidizable carbonaceous species like amorphous carbon [32][33][34]. Furthermore, the comparison between DTA profiles of the fresh and coked catalysts indicated that the fresh catalyst did not contain any coke.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…It has been well accepted that coke formation is the primary reason for the Pt catalyst deactivation in propane dehydrogenation [4,5,58]. There are two types of coke are identified during the dehydrogenation process, graphitic carbon which contains only C atoms arranged in six-membered rings and coke which consists of both C and H atoms with the C/H ratios higher than 0.5 [59].…”
Section: Coke Effectsmentioning
confidence: 99%
“…Apparently, the deactivation of the catalysts can be correlated with the coke content listed in Table 4. The catalyst with higher aluminum content in the support produced higher coke amount as measured by TGA since the acidic sites on alumina could catalyze the coke formation [29]. However, in our previous study, we found that that the coke content was not a main factor in determination of catalytic deactivation.…”
Section: Reaction Testmentioning
confidence: 72%